Integrated water quality monitoring and assessment report: State of Colorado - Lemly, Joanna M., author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2012)
This report is an excerpt of the Wetlands section from the The Colorado 2012 Integrated Water Quality Monitoring and Assessment Report. The Wetlands section provides an overview of selected U.S. Environmental Protection Agency (EPA) funded wetland projects in Colorado, primarily focused on inventory and condition assessment.
Wetlands section of the 2012 Colorado Integrated Water Quality Monitoring Report
Prepared pursuant to Section 303(d) and Section 305(b) of the Clean Water Act. 2012 Update to the 2010 305(b) Report.
Keywords: Colorado; waterbody size; wetlands monitoring; wetland ecology; protection